Candida sp. 99-125 lipase-catalyzed synthesis of ergosterol linolenate and its characterization. (15th May 2019) - He, Wen-Sen; Li, Lingling; Zhao, Jia; Xu, Hanshan; Rui, Jiaxin; Cui, Dandan; Li, He; Zhang, Huijuan; Liu, Xinqi
Highlights: Ergosterol linolenate was successfully synthesized using Candida sp. 99-125 lipase. The products were characterized by FT-IR, MS and NMR. Ergosterol conversion exceeded 92% in 12 h. The physiochemical properties of ergosterol were greatly improved. This route showed great potential for large-scale production of ergosterol ester. Abstract: As a major sterol in edible mushroom, ergosterol has gained much attention owing to its potential bioactivities. However, ergosterol has a high melting point, poor oil solubility and stability, which restrict its scope of application. In this study, an ergosterol ester of α-linolenic acid was successfully and efficiently prepared using Candida sp. 99 - 125 lipase as a biocatalyst. The desired product was confirmed to be ergosterol linolenate using MS, FT-IR, and NMR analyses. Using Candida sp. 99 - 125 lipase, the product conversion exceeded 92% in 12 h under the following optimized parameters: 75 mmol/L ergosterol, 40 g/L lipase, 1:1.25 ergosterol-to-α-linolenic acid molar ratio, and 45 °C. The results confirmed that Candida sp. 99 - 125 lipase has good reusability and stability and is also relatively low cost, suggesting its great potential for large-scale production of ergosterol ester. Most importantly, the physiochemical properties (oil solubility and melting point) of ergosterol significantly improved after esterification with α-linolenic acid, thus facilitating its application in oil-based systems.